Oddział wileński Polskiego Towarzystwa Eugenicznego Walki ze Zwyrodnieniem Rasy w dwudziestoleciu międzywojennym — geneza, działalność i struktura prawna - Dąbrowski, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Vilnius Branch of the Polish Eugenics Society played asignificant role in the development and propagation of eugenic ideas. Statutory goals were realized through the establishment of eugenic and premarital counseling. In addition, alot of attention has been devoted to numerous lectures. The Vilnius society with great approval accepted the establishment of anew institution, and some resistance came from local intelligentsia and doctors.
Keywords: eugenics; Polish Eugenics Society; Vilnius